Board of Governors’ roles and students’ academic Performance in Secondary Schools in Kikagate Sub-County, Isingiro District. - Wilson Mukombe, Bagarukayo (Kabale University, 2020)
The study was about “Board of Governors’ roles and students’ academic performance in Isingiro District. The study was guided by a set of specific objectives which include; To find out whether there is a difference in the level of academic performance across the selected secondary schools in Kikagate Sub-County, To establish the relationship between the Board of Governors’ (BOG) supervisory role and academic performance in Secondary Schools and To examine the relationship between the Board of Governors’ (BOG) budgeting role and academic performance in Secondary Schools. The study employed a cross-sectional survey design where by data was collected from several respondents at one point in time. Out of a target population of 167 respondents, the study used a sample size of 113 respondents. Questionnaires, observation guide, documentary analysis and interview guides were used to collect data from the field. The study employed both Simple Random Sampling and purposive sampling technique. Quantitative data was analyzed using one- way analysis of variance (ANOVA) and Pearson correlation coefficient (r) while qualitative data was analyzed by generating themes from participants’ voices. The study findings indicated that Kamubeizi secondary school performs lower (μ=18.08) than the other schools, while Kyezimbire secondary school performs better (μ=22.18) than the other three secondary schools, followed by Kikagate secondary school (μ=22.11) and Rwamurunga community secondary school (μ=22.07), with students’ scores ranging from 8 (Minimum) to 48 (Maximum) aggregates. The study findings also indicated that board of governors has helped in supervision of the schools’ activities. The study concluded that board of governors has helped in supervision of the schools’ activities which have helped to improve the performance of the students. The study concluded that board of governors has contributed in planning and management of the schools and this has provided a strategic framework within which the school board, the head teacher and staff can monitor, evaluate and improve the nature of the school’s curricular and other provision and the standards achieved by students making efficient use of all the school’s available resources. The study recommended that the Ministry of Education should establish a mandatory training course, conferences, seminars, inductions and workshops for all the Board of Governors to increase their knowledge and skills like financial, human resource management, planning, conceptual, technical skills in efficient management of schools.